4(2p-2)=3(2p+4)

Simple and best practice solution for 4(2p-2)=3(2p+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2p-2)=3(2p+4) equation:


Simplifying
4(2p + -2) = 3(2p + 4)

Reorder the terms:
4(-2 + 2p) = 3(2p + 4)
(-2 * 4 + 2p * 4) = 3(2p + 4)
(-8 + 8p) = 3(2p + 4)

Reorder the terms:
-8 + 8p = 3(4 + 2p)
-8 + 8p = (4 * 3 + 2p * 3)
-8 + 8p = (12 + 6p)

Solving
-8 + 8p = 12 + 6p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-6p' to each side of the equation.
-8 + 8p + -6p = 12 + 6p + -6p

Combine like terms: 8p + -6p = 2p
-8 + 2p = 12 + 6p + -6p

Combine like terms: 6p + -6p = 0
-8 + 2p = 12 + 0
-8 + 2p = 12

Add '8' to each side of the equation.
-8 + 8 + 2p = 12 + 8

Combine like terms: -8 + 8 = 0
0 + 2p = 12 + 8
2p = 12 + 8

Combine like terms: 12 + 8 = 20
2p = 20

Divide each side by '2'.
p = 10

Simplifying
p = 10

See similar equations:

| -3(2-1x)=2x-9 | | 2=-2y+6/13 | | 10y=-5x-15 | | 11x=-42 | | 3+log[4](x+6)=4 | | 0.12x^2-0.72x-0.137=0 | | 100x+100x^2-45=0 | | 2014-1952+-7abc+18=62 | | -2(3x-4)=-(2x-2) | | 0.12x^2+-0.72x+-0.137=0 | | 20x-24=2x | | -11=7-1x | | 45g+7=-6 | | x^3-(2x^2)+1.25x-0.25=0 | | 1952-7abc+18=62 | | 2+2k=8k+3-6k | | x^3-(2x^2)+1.5x-0.25=0 | | 5n-8=n+27 | | [9(y+5)-17]-[3(y-4)+3]= | | 5x-3+7x=45 | | 2+2k=8k+3-6 | | 2(x-2)=3x-4x+5 | | 2x+10=6x-4 | | 7-3(3)=-3+1 | | 17.50-8.75= | | (n+4)-(-3n-7)= | | k/15-13=4 | | 7k^2-54k-16= | | [7(z+5)-17]+[3(z-2)+2]= | | 19abc+18=62 | | 3t=3r-54 | | 12x-10-12=0 |

Equations solver categories